1997
DOI: 10.1007/bf01208639
|View full text |Cite
|
Sign up to set email alerts
|

Increased phospholipase D activity in human breast cancer

Abstract: Phospholipase D is believed to play an important role in cell proliferation and tumorigenesis. One of its major functions is to cause a sustained activation of protein kinase C through the primary production of phosphatidic acid from phosphatidylcholine by the enzyme, followed by dephosphorylation forming diacylglycerol. Protein kinase C is known to be activated or translocated in some tumors including breast tumors. In order to examine phospholipase D activity in breast tumors, surgical specimens of human bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 34 publications
5
72
0
Order By: Relevance
“…Thus, evidence supporting a role for PLD in regulating both growth factor-and oncogene-induced cell proliferation is substantial. And, consistent with this hypothesis, elevated expression of PLD1 has been reported to be common in breast cancer tissues (Uchida et al, 1997;Noh et al, 2000). PLD activity has also been reported to be elevated in renal (Zhao et al, 2000) and gastric (Uchida et al, 1999) cancers and a polymorphism of the PLD2 gene was recently reported to be associated with the prevalence of colorectal cancer (Yamada et al, 2003).…”
Section: Discussionsupporting
confidence: 57%
“…Thus, evidence supporting a role for PLD in regulating both growth factor-and oncogene-induced cell proliferation is substantial. And, consistent with this hypothesis, elevated expression of PLD1 has been reported to be common in breast cancer tissues (Uchida et al, 1997;Noh et al, 2000). PLD activity has also been reported to be elevated in renal (Zhao et al, 2000) and gastric (Uchida et al, 1999) cancers and a polymorphism of the PLD2 gene was recently reported to be associated with the prevalence of colorectal cancer (Yamada et al, 2003).…”
Section: Discussionsupporting
confidence: 57%
“…Participation of PLD-generated PA in downstream signal transduction from mitogenic growth factor receptors via Ras and the MAP kinase pathway has been demonstrated. 12 In comparison with adjacent non-neoplastic tissues, elevated expression and activity of PLD have been detected in various human tumors, including those of breast, 7,31 colorectal, 32,33 gastric, 34 renal 35 and papillary thyroid cancers. 36 Recent clinical studies have reported on correlation of PLD expression levels with tumor size; an association with survival of patients with colorectal carcinoma was also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous levels of PA are low in resting cells, and PLD activity is tightly regulated by mechanisms that control secretion, migration, survival and proliferation of cells. 1,2 PLD is activated by a variety of mitogens, including epidermal growth factor (EGF), platelet-derived growth factor (PDGF) and interleukin 1b (IL-1b), [3][4][5][6][7] and its involvement in many cellular biological processes, including cell proliferation, survival, vesicular trafficking and secretion, has been demonstrated. 1,8 Two distinct isoforms of mammalian PLD, PLD1 and PLD2, have been identified.…”
mentioning
confidence: 99%
“…61 Phospholipase D overexpression has been reported for many cancer types including breast cancer cell lines and tissue samples, as well as renal and gastric cancers and is associated with mTOR-mediated pro-survival phenotypes. [62][63][64][65] Thus, modification of the intracellular phospholipid code by changes in the expression and/or activity of various phospholipid modifiers can ultimately regulate tumor progression.…”
Section: Alteration Of the Phospholipid Code During Tumor Progressionmentioning
confidence: 99%